Preparation for teacher collaboration in inclusive classrooms – stress reduction for special education students via acceptance and commitment training: A controlled study. Issue 1 (December 2015) - Pülschen, Simone; Pülschen, Dietrich
Abstract Background The education system in Germany is beginning to witness a sea change, lately, owing to the country's ratification of the United Nation's Convention on the Rights of Persons with Disabilities. The enactment is aiming at making provision for special education teachers to share the same teaching platform and institution with other teachers for teaching children from all backgrounds, irrespective of their needs. While promoting the benefits of collaborative teaching, this provision would also effectively establish role demarcation among teachers. However, the level of participation and adaptiveness displayed by individual teachers would play a major role in determining the success or failure of the intended collaborative framework. Collaboration also becomes challenging due to the level of stress involved in the teaching profession. The fact that only 65 % of teachers in Germany reach retirement age while still in service, primarily due to psychiatric illness, has posed questions on adopting the collaborative framework for teachers from diverse backgrounds. In other words, it can be stated that the process of collaborating with teachers from different professional backgrounds and with varying levels of skills will potentially lead to further stress. The stress-related psychological states, developed through the collaborative processes, might affect the biological stress-response systems of the participating teachers. With stress-response contributing directly to the pathogenesis of stress-related diseases and disorders in the long term, it would be important to contain the ripple effect of collaborative framework that the enactment intends to establish between SEN (special educational needs) teachers and others. Methods In addition to impacting the long-term health of teachers, the collaborative framework is also suggestive of having similar effects on students studying special education (SEN students). A study was conducted to examine the stress levels associated with the collaborative framework. An expression in terms of two (group affiliation) × 2 (measurement time) between subjects design was implemented to examine the effects of an Acceptance and Commitment Training on the subjective tension of a sample (N = 68) of SEN students. The sample was split into an intervention and a control group (IG and CG). The effects of the training on collaborative competence were examined using the Chi-square test. Questionnaire and role plays were used to assess the collaborative competence and the subjective tension. Results The participants had significant stress levels and displayed an uncooperative attitude during the initial assessment. However, these results reversed after the Acceptance and Commitment Training. Significant decrease in stress levels and improved cooperation were evident among the participants in the intervention group, as opposed to the participants of the control group. Conclusions The findings of this study show that the Acceptance and Commitment Training is an appropriate medium to establish and develop collaboration skills, and an effective technique to reduce high levels of subjective stress. Furthermore, the training evaluation and feedback indicate that it is well-accepted by all participants. The training is also endorsed as a practically relevant medium to help SEN students collaborate and combat stress.